Microencapsulation of Umami Flavor Enhancer from Indonesian Waters Brown Seaweed. - NURHIDAJAH; PRANATA, BOBY; YUSUF, MUHAMMAD; KHOLIFATUDDIN SYA'DI, YUNAN; YONATA, DIODE (Current Research in Nutrition & Food Science, 2022)
Sargassum aquifolium is a type of brown seaweed that grows in Indonesian waters. The L-glutamic acid in Sargassum aquifolium extract can be optimized to be a natural umami flavor enhancer. Spray drying is used for the manufacture of umami flavor enhancing microcapsules, where the core ingredient (extract of Sargassum aquifolium) is coated with 10, 20, and 30% (w/v) Maltodextrin (MD). The increase in coating material caused the water content, water activity, and hygroscopicity of the microcapsules to decrease significantly. This is followed by an increase in bulk and tapped density, as well as powder flowability. The particle size distribution is getting smaller, with smooth surface morphology and uniform shape, and the microcapsule L-glutamic acid levels increased with the addition of the MD concentration. The increase in coating material had a negative impact on the wettability time of the flavor enhancer, the color of the product was slightly degraded but the brightness increased significantly. Meanwhile, the water soluble index and water absorption index for microcapsules did not increase the coating material's increase. In conclusion, the best umami flavor enhancing microcapsules from Sargassum aquifolium seaweed extract was produced by adding 30% MD coating material which was dried by spray drying.